2018
DOI: 10.1111/jcpt.12725
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera leaf powder alters the pharmacokinetics of amodiaquine in healthy human volunteers

Abstract: The study established pharmacokinetic interaction between AQ and MO when given together or following a long period of ingestion of MO. This may have clinical implications for malaria therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…For example, it has been shown that a pharmacokinetic interaction exists between the antimalarial drug amodiaquine and Moringa oleifera Lam., a commonly used medicinal plant with multiple health benefits, when given together or following a long period of ingestion of Moringa oleifera Lam. In the presence of Moringa oleifera Lam., the peak plasma concentration of amodiaquine decreased by up to 40%, as well as its area under the plasma concentration-time curve which decreased by approximately 11%, leading to a significantly delayed absorption of amodiaquine (Olawoye et al, 2018). Overall, establishing herbal toxicity can be difficult.…”
Section: Challenges Associated With the Herbal Medicine Practicementioning
confidence: 99%
“…For example, it has been shown that a pharmacokinetic interaction exists between the antimalarial drug amodiaquine and Moringa oleifera Lam., a commonly used medicinal plant with multiple health benefits, when given together or following a long period of ingestion of Moringa oleifera Lam. In the presence of Moringa oleifera Lam., the peak plasma concentration of amodiaquine decreased by up to 40%, as well as its area under the plasma concentration-time curve which decreased by approximately 11%, leading to a significantly delayed absorption of amodiaquine (Olawoye et al, 2018). Overall, establishing herbal toxicity can be difficult.…”
Section: Challenges Associated With the Herbal Medicine Practicementioning
confidence: 99%
“…The crude preparation of the plant leaves in aqueous form also demonstrated antimalarial activities by suppressing P. berghei ANKA infection in mice (137). Very recently, Olawoye et al (138) studied the actions of M. oleifera powdered leaves on amodiaquine (AQ) pharmacokinetics in healthy twenty human volunteers and established a positive interaction between AQ and M. oleifera suggesting a possible combinatorial therapy for malaria. The methanolic seed extract of M. oleifera also exhibited significant insecticidal activities, which could be exploited for integrated pest management to control the Anopheles mosquito (139).…”
Section: Anti-malaria Activitiesmentioning
confidence: 99%
“…This recommendation is especially useful when considering the use of moringa leaves as an ingredient in fortifying foods of infants whose bodies are at crucial stages of development. A study by Olawoye et al (2018) also revealed that there was a pharmacokinetic interaction between amodiaquine, a popular drug for the treatment of malaria, and MLP when given together or following a long period of ingestion of MLP (Olawoye et al, 2018). This finding is particularly important, as it indicates that the presence of MLP may alter the amount of amodiaquine absorbed, thus resulting in either subtherapeutic or toxic serum levels (Olawoye et al, 2018).…”
Section: The Way Forwardmentioning
confidence: 99%
“…A study by Olawoye et al (2018) also revealed that there was a pharmacokinetic interaction between amodiaquine, a popular drug for the treatment of malaria, and MLP when given together or following a long period of ingestion of MLP (Olawoye et al, 2018). This finding is particularly important, as it indicates that the presence of MLP may alter the amount of amodiaquine absorbed, thus resulting in either subtherapeutic or toxic serum levels (Olawoye et al, 2018). Given that MLP is being considered for use in infant and young child populations in low-resource settings where malaria is likely to be endemic, there is a high possibility of simultaneous administration of MLP with anti-malarials with little known ramifications, if infants NFS 49,3 are fed with complementary foods fortified with MLP.…”
Section: The Way Forwardmentioning
confidence: 99%